The Relationship between the Quality of the Online Registration System and the Satisfaction of Klinisia Application Users at the Ciracas District Health Center - silviani; Martini; Harahap, Sarah Geltri (LPPM Universitas Dhyana Pura, 2025)
Digital transformation in the healthcare sector has driven the use of information technology to improve service quality, including through online registration systems at community health centers. However, the implementation of such systems still faces several challenges, such as an unattractive interface, a difficult registration process, and Limited- service options. This study aims to examine the relationship between the quality of the online registration system in the Klinisia application and user satisfaction at the Ciracas District Health Center in 2025. A quantitative method with a cross-sectional approach was used. A total of 376 respondents were selected using accidental sampling. The results showed that respondents’ assessments of system quality dimensions were as follows: Flexibility good 87,2%, poor 12,8%; Reliability good 87,8%, poor 12,2%, System Integration good 88,3%, poor 11,7%; System Accessibility good 90,4%, poor 9,6%; and Response Time good 90,4%, poor 9,6%. Statistical analysis indicated a significant relationship between all system quality dimensions and user satisfaction (P-Value < 0.05). It can be concluded that the quality of the online registration system is significantly associated with patient satisfaction and contributes to faster service processes and improved service effectiveness at the health center.